Assessment of patient capability to self-adjust oral anticoagulant dose: a multicenter study on home use of portable prothrombin time monitor (COAGUCHECK) - Cosmi, B; Palareti, G; Carpanedo, M; Pengo, V; Biasiolo, A; Rampazzo, P; Morstabilini, G; Testa, S (Haematologica (Roma), 2000)
Divisione di Angiologia, Ospedale S.Orsola Malpighi, Bologna, Italy. BACKGROUND AND OBJECTIVES: Self-testing and self-monitoring with portable prothrombin time (PT) monitors has been shown to be feasible and safe. However the ability of patients on chronic oral anticoagulant therapy (OAT) to self-adjust their dose without specific training has never been properly evaluated. The aims of this study were to evaluate: 1) the ability of patients on chronic OAT to self-adjust their dose without specific training; 2) the integration of a portable PT monitor (Coagucheck, Roche Diagnostics, Germany) for home use into routine patient care in anticoagulation clinics. DESIGN AND METHODS: A nested case-control study was conducted in four centers of the Italian Federation of Anticoagulation Clinics (FCSA). Patients (n=78) on stable OAT for at least 6 months (cases: 47 men, 31 women, age range: 18-75 years) were enrolled on a volunteer basis after passing an Abbreviated Mental Test and providing informed consent. After three instruction sessions on the use of Coaguchek, subjects performed the PT test at home, communicated the INR results to the Center and suggested the dose adjustment and date for next control as they thought appropriate. However, they were requested to follow the prescription made by the Center. Controls (78 subjects) matched by age (+/- 5 years), sex and therapeutic range with the cases, were selected from among those who attended the anticoagulation clinics and managed by usual care. RESULTS: When compared with the dose prescribed by the Clinic, the dose suggested by warfarin and acenocoumarol users was equal to or within +/- 6% of the mean weekly dose in 80% and 82% of suggestions, respectively. Time spent in the therapeutic range during the study was the same (80%) for cases and controls. INTERPRETATION AND CONCLUSIONS: Selected patients on chronic anticoagulant therapy can acquire a satisfactory ability for self-adjustment of OAT dose without specific training.